Effect of the relative permittivity of oxides on the performance of triboelectric nanogenerators. Issue 78 (23rd October 2017) - Kim, Yeon Joo; Lee, Jaejun; Park, Sangwon; Park, Chanho; Park, Cheolmin; Choi, Heon-Jin
Abstract : The influence of the relative permittivity of dielectric materials on the performance of TENGs, by controlling the positive plate with various oxide materials, has been demonstrated. Abstract : Since the working mechanism of triboelectric nanogenerators (TENGs) is based on triboelectrification and electrostatic induction, it is necessary to understand the effects of the inherent properties of dielectric materials on the performance of TENGs. In this study, the relationship between the relative permittivity and the performance of TENGs was demonstrated by fabricating TENGs using both pure oxide materials (SiO2, Al2 O3, HfO2, Ta2 O5 and TiO2 ) and oxide–PMMA composites. As oxide materials and PMMA are triboelectrically positive, PTFE film was selected as the counter tribo-material, which has highly negative triboelectric polarity. The triboelectric series of the above-mentioned oxides was experimentally organized to clarify the major parameter for the performance of TENGs. The electrical data values for both oxides and composites clearly showed a tendency to increase as the relative permittivity of the tribo-material increased. It is also well-matched with the theoretical analysis between the electrical performances ( e.g. open-circuit voltage) and relative permittivity. However, such a tendency is not observed with the triboelectric polarity. Due to the tribo-material's high relative permittivity, an open-circuit voltage of 124.1 V, a short-circuit current of 14.88 μA and a power of 392.08 μW were obtained in a pure TiO2 thin film.